Rich and Balanced Experiences of Daily Emotions Are Associated With Activity Diversity Across Adulthood. (3rd August 2021) - Lee, Soomi; Urban-Wojcik, Emily J; Charles, Susan T; Almeida, David M
Abstract: Objectives: Studies demonstrate the association between diverse emotions and health. However, we know little about how these emotions are related to activities in daily life. This study examined whether the diversity of daily activities ("activity diversity") is associated with the diversity of both positive and negative daily emotions ("emodiversity") in adulthood. We also examined if these associations differed by age. Method: 2 separate samples of participants from the Midlife in the United States Study II (M2: 2004–2009, n = 2, 012, M age = 56 years) and Refresher (MR: 2012–2016, n = 779, M age = 47 years) provided activity and emotion data for 8 consecutive days. Using Shannon's entropy, we constructed activity diversity and emodiversity (positive, negative) scores. Analyses adjusted for sociodemographic and health characteristics, total activity time, mean positive/negative emotions, and number of days with positive/negative emotion data. Results: Greater activity diversity was associated with greater positive emodiversity and greater negative emodiversity in both samples. In the M2 sample, the association between activity diversity and positive emodiversity was stronger among relatively younger adults, such that the positive association among those aged 33–44 years was greater than that observed among those aged 68–84 years. Results held after adjusting for time spent in each of the activities or when using different emodiversity metrics (Gini or Simpson coefficients). Discussion: Broad and even participation of daily activities may provide more opportunities to experience rich and balanced emotions. Findings suggest that the association between activity diversity and emodiversity exists across adulthood, underscoring the value of including information about daily activities when examining emotional experiences across the life span.